Colloidal particles in competition for stabilizer a solvent relaxation NMR study of polymer adsorption and desorption - Cooper, Catherine L (Langmuir : the ACS journal of surfaces and colloids, 2012)
The competitive adsorption of poly(vinylpyrrolidone) onto silica and alumina-modified silica particles was studied using solvent relaxation nuclear magnetic resonance. The additive nature of the measured relaxation rate enabled predictions to be made of the relaxation rate in different polymer adsorption scenarios. Preferential adsorption of the poly(vinylpyrrolidone) onto the unmodified silica particles occurred when there was insufficient polymer in the system to coat the entire available surface area. Desorption was also found to occur when the polymer was initially adsorbed upon the alumina-modified particle and silica particles were added